A Comparative Analysis of English Learning Motivation between the Rural and Urban Students - Agus Rahmat; Muhammad Akbar (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
The objectives of this research are to find out (1) the motivation of the rural and urban students (2) the types of motivation influence the rural and urban students (3) the factors influence the motivation of the rural and urban students (4) the effective ways to foster the motivation of the rural and urban students. This research employed descriptive qualitative research design. The subject of this research is the ninth grade students of MTs Muhammadiyah Lempangang as urban students and the ninth grade students of MTs N 4 Bulukumba as rural students. The number of participants is 20 students. The result of research showed that (1) all of the informants of MTs N 4 Bulukumba as a rural area are motivated in Learning EFL. It is similar with the informants of MTs Muhammadiyah Lempangang as an urban area. They are also motivated. Both of areas are different in the level of motivation(2)the types of motivation dominantly influence in the rural students are both of integrative and instrumental motivation whereas in the urban students are instrumental motivation(3)the similarity between both of students area either internal or external factors are the expectancy, the teachers and the activities and materials whereas the difference from both of them are the relevance, the goal setting and the school environment(4)the effective ways to foster the motivation of the rural students in learning EFL is the teacher always trains the pronunciation of the vocabulary whereas the urban students is the teacher should have more practice activity in learning and teaching process.